Concevoir Une Société Yacouba Sans La Pratique De L’excision, Une Équation Impossible ? - Adolphe, Kouadıo Kouassi Kan; Thédore, Doudou Dimi; Donoukporo, Tuo (European Scientific Journal, ESJ, 2017)
The practice of violence against women is becoming increasingly acute in Côte d’Ivoire. The forms and frequencies vary from one cultural area to another. Thus, in the west, in the Tonkpi, female genital mutilation (FGM), occupy the heights of forms of gender-based violence (GVA), (CRD, 2016). In order to identify the strategies of circumcisers in this period of prohibition of FGM and the representations that underpin this practice, in spite of national and international policies, research was carried out in three sub-prefectures of the department of Man and Biankouma from February to March 2016. This is a qualitative study. The results confirmed that the attachment to custom and the adoption of new strategies are the factors explaining the persistence of the practice of excision in Côte d’Ivoire.